Saccharin Revisited: Chemistry, Metabolism, Toxicology and Human Health Risk Assessment in the Era of Evidence‐Based Food Safety - Amjad Mahmood Qadir; Azad Mohammed Aziz Ahmed; Musa M. Zorab; Rebaz Anwar Omer (Journal of Applied Toxicology, 2026)
ABSTRACT Saccharin is one of the oldest and most extensively used nonnutritive sweeteners, valued for its intense sweetness, chemical stability and negligible caloric contribution. Since its discovery in 1879, it has been widely incorporated into foods, beverages, pharmaceuticals and personal care products, while its safety has remained the subject of considerable scientific and regulatory debate. Early experimental studies linking saccharin to bladder tumour formation in rodents raised concerns regarding its carcinogenic potential; however, subsequent mechanistic investigations, epidemiological evidence and comprehensive risk assessments have demonstrated that these findings are species‐specific and not directly applicable to humans. This review provides a comprehensive and critical synthesis of current knowledge on saccharin, encompassing its chemical characteristics, physicochemical properties, industrial and pharmaceutical applications, absorption, metabolism, excretion and toxicological profile. Particular emphasis is placed on evaluating evidence related to carcinogenicity, genotoxicity, metabolic effects, oxidative stress, gut microbiota interactions and other emerging health concerns through the integration of experimental, clinical and population‐based studies. In addition, the review examines the scientific basis of international regulatory decisions, discusses the challenges of translating animal toxicology findings into human health risk assessment and identifies persistent knowledge gaps requiring further investigation. Current evidence consistently supports the safety of saccharin when consumed within established acceptable daily intake limits established by international regulatory agencies. Nevertheless, well‐designed long‐term human studies and mechanistic investigations remain necessary to better define its potential effects on metabolic health, the gut microbiome and susceptible populations. By integrating historical evidence with contemporary advances in toxicology and regulatory science, this review provides an updated framework for understanding the safety, biological effects and public health implications of saccharin consumption.